Relation of Capital-Output Ratio to Firm Size in American Manufacturing: Some Additional Evidence - Davis, Hiram S. (The Review of Economics and Statistics, 1956)
M OST writers about the relation of capital to output in American manufacturing have been impressed by the tendency for the ratio to increase with size of firm. They have usually emphasized one explanation, although they have not agreed on the one that should be stressed. It is the purpose of this paper to present evidence not readily available that the tendency may not be as universal as often assumed and that, where it exists, the explanation is likely to differ from one industry to another. The usual analysis of capital ratios for American manufacturing has been based upon the industrial aggregates compiled by the Internal Revenue Service (formerly Bureau) of the Treasury Department.2 Accordingly it has not been possible for the investigator to analyze the capital ratios of each firm in relation to those of other firms with which commonly classified. In contrast, it was possible in the study reported here to examine the behavior of the ratios for each industry, firm by firm.3